The association between tobacco control policy implementation and country-level socioeconomic factors in 31 European countries - Feliu, Ariadna (Sci Rep, 2021)
European countries have made significant progress in implementing tobacco control policies to reduce tobacco use; however, whether socioeconomic status (SES) of a country may influence the implementation of such policies is unknown. The aim of this study is to assess the association between country-level SES and the implementation level of tobacco control policies in 31 European countries. An ecological study using data from Eurostat, Human Development Reports on several SES indicators and the Tobacco Control Scale (TCS) of 2016 was conducted to measure country-level tobacco control policies. We analysed the relationship between SES indicators and the TCS by means of scatter-plots and Spearman’s rank correlation coefficients (r(sp)) and multivariable linear regression analysis. In Europe, no statistically significant association was found between SES factors and the level of implementation of tobacco control policies. Only public spending on tobacco control was associated with all SES factors, except for Gini Index (an income inequality index). The strongest associations of TCS scores for this policy domain were found with the Human Development Index (r(sp) = 0.586; p < 0.001) and the Gross Domestic Product per capita (in Euros) (r(sp) = 0.562; p = 0.001). The adjusted linear regression model showed an association of tobacco control policy implementation with countries’ geographical location (Western Europe, β = − 15.7; p = 0.009, compared to Northern Europe). In conclusion, no association was found between SES factors and the level of implementation of tobacco control policies in 31 European countries; policymakers should be aware that tobacco control policies could be successfully implemented despite socioeconomic constraints, especially when these policies are of low cost and cost-effective (i.e., smoke-free bans and taxation).